2013
DOI: 10.1088/0031-9155/58/22/8163
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory optimization for dynamic couch rotation during volumetric modulated arc radiotherapy

Abstract: Abstract. Non-coplanar radiation beams are often used in three-dimensional conformal and intensity modulated radiotherapy to reduce dose to organs at risk (OAR) by geometric avoidance. In volumetric modulated arc radiotherapy (VMAT) non-coplanar geometries are generally achieved by applying patient couch rotations to single or multiple full or partial arcs. This paper presents a trajectory optimization method for a non-coplanar technique, dynamic couch rotation during VMAT (DCR-VMAT), which combines ray tracin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
93
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(94 citation statements)
references
References 34 publications
1
93
0
Order By: Relevance
“…[46][47][48][49] Leaving potential issues regarding patient immobilization on a robotic couch aside, the first treatment planning studies investigating noncoplanar VMAT have reconfirmed a benefit of noncoplanar irradiation with regard to OAR sparing. 33,45,47,[50][51][52][53] From the mathematical and technical side, the optimization of an irradiation trajectory shares the known issues of beam angle optimization (BAO) for step&shoot IMRT. When viewed as a continuous optimization problem, BAO is highly nonconvex.…”
Section: E Noncoplanar Generalizations Of Vmatmentioning
confidence: 99%
See 1 more Smart Citation
“…[46][47][48][49] Leaving potential issues regarding patient immobilization on a robotic couch aside, the first treatment planning studies investigating noncoplanar VMAT have reconfirmed a benefit of noncoplanar irradiation with regard to OAR sparing. 33,45,47,[50][51][52][53] From the mathematical and technical side, the optimization of an irradiation trajectory shares the known issues of beam angle optimization (BAO) for step&shoot IMRT. When viewed as a continuous optimization problem, BAO is highly nonconvex.…”
Section: E Noncoplanar Generalizations Of Vmatmentioning
confidence: 99%
“…For the second step, all VMAT methods discussed in this paper can be applied with minor adjustments. The trajectories used for the above treatment planning studies were either found through inspection by a human planner, [50][51][52] using geometric heuristics, 45,53 or exhaustive search considering nine different couch tilts. 47 Wild et al 33 use a noncoplanar beam ensemble which was optimized with a genetic algorithm 49 for step&shoot IMRT to construct a noncoplanar VMAT trajectory.…”
Section: E Noncoplanar Generalizations Of Vmatmentioning
confidence: 99%
“…In addition, they involved sporadic couch movements, which are both uncomfortable, can result in intra‐fraction motion and require complex quality assurance (QA) protocols. While previous methods successfully presented the dosimetric benefits of a trajectory‐based delivery, they did not systematically study the dosimetric benefits of trajectory modulation. It is therefore difficult to assess whether the dosimetric benefits of trajectory‐based deliveries were fully utilized by these methods.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment planning studies went even further, exploring the possible benefits of VMAT delivery simultaneously with couch rotations (4)(5)(6). Other groups such as Yang et al (7) and Smyth et al (8) have additionally developed direct trajectory optimization methods to identify optimal 3D radiation delivery trajectories. All these studies share the same disadvantage in that the treatment couch needs to be changed during gantry rotation, which might introduce patient movement and potential collision.…”
Section: Introductionmentioning
confidence: 99%